Sampled-Data H∞ Dynamic Output Feedback Controller Design for Fuzzy Markovian Jump Systems - Lin, Yuqian; Zhuang, Guangming; Xia, Jianwei; Chen, Guoliang; Lu, Junwei (Journal of systems science and complexity, 2023)
This paper considers the issue of H ∞ dynamic output feedback controller design for T-S fuzzy Markovian jump systems under time-varying sampling with known upper bound on the sampling intervals. The main aim is to realize sampled-data fuzzy dynamic output feedback control so as to demonstrate the stochastic stability and H ∞ performance index of the closed-loop sampled-data fuzzy Markovian jump systems. Then, by making the most of the information within the sampling interval, a suitable closed-loop function is constructed and the integral terms are handled by using free weighted matrix method and improved integral inequality technique. Numerical example and single-link robot arm are presented to show the effectiveness of the developed method.